Proceedings of the 10th Annual Conference on Genetic and Evolutionary Computation 2008
DOI: 10.1145/1389095.1389130
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative network construction using digital germlines

Abstract: This paper describes a study in the evolution of cooperative behavior, specifically the construction of communication networks, through digital evolution and multilevel selection. In digital evolution, a population of self-replicating computer programs exists in a user-defined computational environment and is subject to instruction-level mutations and natural selection. Multilevel selection links the survival of the individual to the survival of its group, thus encouraging cooperation. The results of experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…The use of a digital germline has the side-effect of homogenizing the inhabitants of each deme, a technique that has been effective in evolutionary robotics [10]. Moreover, in an earlier study, we observed that using a digital germline was necessary to evolve organisms that cooperated to construct communication networks [16].…”
Section: Get-cyclesmentioning
confidence: 95%
See 1 more Smart Citation
“…The use of a digital germline has the side-effect of homogenizing the inhabitants of each deme, a technique that has been effective in evolutionary robotics [10]. Moreover, in an earlier study, we observed that using a digital germline was necessary to evolve organisms that cooperated to construct communication networks [16].…”
Section: Get-cyclesmentioning
confidence: 95%
“…To encourage the evolution of cooperation, we also employed digital germlines [16], a framework that provides a single common genetic ancestry for all organisms within a deme. In AVIDA, the germline is a genome attached to a deme, rather than to an individual.…”
Section: Get-cyclesmentioning
confidence: 99%
“…DIGITAL EVOLUTION AND AVIDA Digital evolution [9] is a form of evolutionary computation originally developed to study evolution in biology. AVIDA [10], a platform for digital evolution, has also recently been applied to engineering problems, including the construction of communication networks [11] and adaptive population control for energy efficiency [12]. Although AVIDA has many characteristics that make it suitable for studying evolution in biology, here we use AVIDA similarly to a linear genetic program [25].…”
Section: Related Workmentioning
confidence: 99%
“…Digital organisms in AVIDA exist in a spatial environment, communicate with their neighbors, and execute their "genome," a list of virtual CPU instructions. Recently, AVIDA has been applied to an increasingly diverse set of engineering problems, from the construction of communication networks [11] to adaptive population control [12].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we observe how populations reacted when the degree of adversity in the environment changed or when they were exposed to threats which they had not encountered in hundreds of generations. [19].…”
Section: Introductionmentioning
confidence: 99%